The Influence Of Perceived Security, Perceived Behavioural Control, And Social Influence On Behavioural Intention Indonesian Standard Quick Response (Qris) On Gen-Z In Batam City - Mahendra, Rizky Adi; Estin Rose Eviyani; Inda Meyllya Putri; Destiana Safitri; Johny Budiman (Economos : Jurnal Ekonomi dan Bisnis, 2024)
Along with the rapid development of technology makes all human activities more effective and efficient from various fields, especially in the financial sector. One proof of the progress in the application of technological innovation in the financial industry is the cashless payment method. One method of non-cash payment is Quick Response Code Indonesian Standard (QRIS). Bank Indonesia intensively conducts socialization related to QRIS, so that QRIS is increasingly known to the wider public and attracts a larger market. This study aims to analyze the factors of perceived security, perceived behavioural control, and social influence on the behavioural intention of Quick Response Indonesia Standard (QRIS) in gen-Z in Batam City. This study used non-probability samples with purposive sampling method. Purposive sampling is a sampling method that considers certain features to obtain a goal. In this study also using analytical methods carried out in two stages, namely external model analysis and inner model analysis. Outside model evaluation assesses the validity and reliability of indicators of each variable, whereas inner model analysis investigates research hypotheses. For data analysis we use SmartPLS software version 3.0. The results showed that perceived behavioral control significantly affected behavioral intention, peceived security had a significant effect on behavioral intention, and social influence did not have a significant effect on behavioral intention.